Effects of Extracts and Fractions of Gynura procumbens on Rat Atrial Contraction - Omar Saad, Saleh Abrika; Yam, Mun Fei; Mohd. Zaini, Asmawi; Amirin, Sadikun; Dieng, Hamady; Elssanousi, Ali Hussain (International Pharmacopuncture Institute, 2013)
There is currently a great deal of research interest in utilizing plant compounds against human diseases, including hypertension. The present study investigated the effects of different extracts and fractions from leaves of Gynura procumbens Merr. on rat atrial contraction in vitro. Isolated left and right atria, mounted in a 20-ml organ bath, were allowed to equilibrate for 15 min before the application of the extracts or fractions. The extracts (petroleum-ether extract (PE) and methanol extract (ME)) and the fractions (chloroform fraction (CHL), ethyl-acetate fraction (EA), n-butanol fraction (NB) and water fraction (WA) of the methanol extract) were tested at three concentrations (0.25, 0.5 and 1.0 mg/ml), with a b-adrenergic agonist (isoprenaline) as a control. All data on contraction responses were log-transformed and analyzed. When exposed to the different extracts, both atria tended to exhibit greater contractive responses with the NB whereas cardiac contractions had a tendency to be reduced with most other extracts. For a given extract, the contraction responses were particularly greater at 0.5 mg/ml for the right atrium and at 1 mg/ml for the left atrium. Further analysis focusing on the NB fraction revealed that positive inotropism was greater in left atria exposed to highly-concentrated F2 and F3 sub-fractions. Taken together, our results suggest that NB extracts and fractions from the G. procumbens-leaf methanol extract have positive inotropic activities and, hence, can be considered as an alternative/traditional medicine against increased blood pressure in humans or can be used in strategies aimed at finding antihypertensive biomolecules from an accessible source.